2021
DOI: 10.3390/ijms22179176
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles as Emerging Players in Intercellular Communication: Relevance in Mast Cell-Mediated Pathophysiology

Abstract: Mast cells are major effector cells in eliciting allergic responses. They also play a significant role in establishing innate and adaptive immune responses, as well as in modulating tumor growth. Mast cells can be activated upon engagement of the high-affinity receptor FcεRI with specific IgE to multivalent antigens or in response to several FcεRI-independent mechanisms. Upon stimulation, mast cells secrete various preformed and newly synthesized mediators. Emerging evidence indicates their ability to be a ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…Recently, a vast array of studies have suggested that in various tumor types, tumor-derived exosomes play an important role in information transmission between tumor cells and the corresponding microenvironment during tumor progression (18,19). In addition, exosomes derived from other different types of cells, such as macrophages (20), mast cells (21), fibroblasts (22), and mesenchymal stem cells (23), mediate bidirectional crosstalk with tumor cells. In HCC, tumor-derived exosomes have the power to activate HSCs by triggering Hedgehog (24) and PDK1/AKT signalling (25) to promote tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a vast array of studies have suggested that in various tumor types, tumor-derived exosomes play an important role in information transmission between tumor cells and the corresponding microenvironment during tumor progression (18,19). In addition, exosomes derived from other different types of cells, such as macrophages (20), mast cells (21), fibroblasts (22), and mesenchymal stem cells (23), mediate bidirectional crosstalk with tumor cells. In HCC, tumor-derived exosomes have the power to activate HSCs by triggering Hedgehog (24) and PDK1/AKT signalling (25) to promote tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Microvesicles serve as vehicles for intercellular communication, with both resting and degranulating mast cells capable of secreting microvesicles. Recent reports have also documented that microvesicles derived from T cells can activate mast cells ( 38 , 39 ), which is mentioned below. These studies highlight new possibilities beyond cell-to-cell contacts or soluble mediators in functional interrelationships between mast cells and other cells.…”
Section: Introductionmentioning
confidence: 88%
“…Previous studies have shown that MRGPRX2 and MRGPRX2 containing vesicles are found in the serum of atopic individuals to release exocytosis and plasma membrane budding ( 126 ). Mast cell-derived extracellular vesicles interact with other cells located nearby or far away, regulating inflammation; and allergic reactions ( 39 ). Whether mast cells communicate with other cells in this way remains to be verified in CSU.…”
Section: The Crosstalk Of Immune Cells In Csumentioning
confidence: 99%
“…On the other hand, MCs may contribute to the tumorigenesis of aggressive human cancers via versatile mechanisms, including extracellular matrix degradation. Through their specific proteases [ 17 , 18 , 19 , 20 ], MCs are involved in degradation of the matrix, which is required for tumor spread [ 16 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%